Types of species described by M.P. Graells (1809-1898) found in the Real Colegio Alfonso XII (San Lorenzo del Escorial, Madrid) - Perea, Domingo; García, Alfonso; Carrasco de Salazar, María Andrea (Botanica Complutensis, 1996)
Sin resumen